Production changes in Ghana cocoa farming households under market reforms - Teal, F; Vigneri, M (CSAE (University of Oxford), 2004)
The Ghana cocoa market has been extensively liberalised over the period since the mid 1980s. Three issues have been prominent in microeconomic research on the effects of liberalisation on agriculture. The first has been the size of any supply response, the second has been the effect on producers of reduced subsidies on inputs, and the third whether innovation has occurred. In this paper we investigate these issues by estimating a production function for cocoa in Ghana drawing on two household surveys covering the period from 1991 to 1998. The estimated production function allows identifying the factors underlying the change in output. The analysis of the micro data shows that the increase in household output has been very modest at 6 per cent. While the effect of liberalisation has been to raise the price of inputs we find that the contribution of such inputs to cocoa production has increased both relative to land and, very substantially, relative to labour. The ratio of both land and nonlabour inputs to labour rose implying a rise in labour productivity of 39 while land productivity was unchanged. We find no evidence that reforms have led to innovation in techniques which raise total factor productivity. Possible reasons for these outcomes are suggested.